Assessment of Different Quit Smoking Methods Selected by Patients in Tobacco Cessation Centers in Iran - Heydari, Gholamreza (Int J Prev Med, 2015)
BACKGROUND: Health systems play key roles in identifying tobacco users and providing evidence-based care to help them quit. This treatment includes different methods such as simple medical consultation, medication, and telephone counseling. To assess different quit smoking methods selected by patients in tobacco cessation centers in Iran in order to identify those that are most appropriate for the country health system. METHODS: In this cross-sectional and descriptive study, a random sample of all quit centers at the country level was used to obtain a representative sample. Patients completed the self-administered questionnaire which contained 10 questions regarding the quality, cost, effect, side effects and the results of quitting methods using a 5-point Likert-type scale. Percentages, frequencies, mean, T-test, and variance analyses were computed for all study variables. RESULTS: A total of 1063 smokers returned completed survey questionnaires. The most frequently used methods were Nicotine Replacement Therapy (NRT) and combination therapy (NRT and Counseling) with 228 and 163 individuals reporting these respectively. The least used methods were hypnotism (n = 8) and the quit and win (n = 17). The methods which gained the maximum scores were respectively the combined method, personal and Champix with means of 21.4, 20.4 and 18.4. The minimum scores were for e-cigarettes, hypnotism and education with means of 12.8, 11 and 10.8, respectively. There were significant differences in mean scores based on different cities and different methods. CONCLUSIONS: According to smokers’ selection the combined therapy, personal methods and Champix are the most effective methods for quit smoking and these methods could be much more considered in the country health system.